Basic Profile of Early Childbirth in the Dominican Republic - Male, Chata; Wodon, Quentin (World Bank, Washington, DC, 2016)
Measures of early childbirth are high in the Dominican Republic. The share of women ages 18-22 who had a child before 18 is 20.4 percent and it has not decreased much over time. The share of girls who had a child before the age of 15, at just under two percent, decreased. Early childbirth is associated with lower wealth, lower education levels, and employment without cash earnings. These are however only correlations, not necessarily causal effects. In order to design programs and policies to reduce the prevalence of early childbirth, information is needed on its trend over time, where it is most prevalent in a country, and what the characteristics of girls giving birth early are.